Assessing the impact on intestinal microbiome and clinical outcomes of antibiotherapy optimisation strategies in haematopoietic stem cell transplant recipients: study protocol for the prospective multicentre OptimBioma study. Issue 7 (20th July 2020) - Jiménez-Jorge, Silvia; Labrador-Herrera, Gema; Rosso-Fernández, Clara M; Rodríguez-Torres, Nancy; Pachón-Ibáñez, María Eugenia; Smani, Younes; Márquez-Malaver, Francisco José; Limón Ramos, Carmen; Solano, Carlos; Vázquez-López, Lourdes; Kwon, Mi; Mora Barrios, Joan Manuel; et al.
Abstract : Introduction: Haematopoietic stem cell transplantation (HSCT) is a life-saving treatment for a number of haematological diseases. Graft versus host disease (GVHD) is its main complication and hampers survival. There is strong evidence that intestinal microbiota diversity of the recipient may increase the risk of GVHD worsening survival. Antibiotic regimens used during the early phase of the transplant may influence clinical outcomes by reducing intestinal microbiota diversity. Present guidelines of European Conference on Infections in Leukaemia exhort to optimising antibiotic use in haematological patients including HSCT recipients. The present study aims to investigate if, in HSCT recipients, the optimisation of antibacterial use may preserve intestinal microbiota composition reducing the incidence and severity of acute GVHD and improving relevant clinical outcomes. Methods and analysis: This is a prospective longitudinal observational study of two cohorts of HSCT recipients: (1) the intervention cohort includes patients treated in centres in which a predefined strategy of antibiotherapy optimisation is implemented, with the objective of optimising and reducing antibiotic administration according to clinical criteria and (2) the control cohort includes patients treated in centres in which a classic permissive strategy of antibiotic prophylaxis and treatment is used. Adult patient receiving a first HSCT as a treatment for any haematological condition are included. Clinical variables are prospectively recorded and up to five faecal samples are collected for microbiota characterisation at prestablished peritransplant time points. Patients are followed since the preconditioning phase throughout 1-year post-transplant and four follow-up visits are scheduled. Faecal microbiota composition and diversity will be compared between both cohorts along with acute GVHD incidence and severity, severe infections rate, mortality and overall and disease-free survival. Ethics and dissemination: The study was approved between 2017 and 2018 by the Ethical Committees of participant centres. Study results will be disseminated through peer-reviewed journals and national and international scientific conferences. Trial registration number: NCT03727113